Restaurant locator using Djikstra Algorithm / Mohamad Aliff Hakimi Lukman Hakim - Lukman Hakim, Mohamad Aliff Hakimi (2017)
Imagine you are hungry and want to drive from a house to a restaurant that serves delicious food. People usually hard to identify the best route to get to the desired location without any navigation tools. As a result, they can be easily lost in the unfamiliar area. People will normally refer to the signboards or ask around for direction in which will either ending up reaching the destination or the other way round. These will definitely causing loosing lots of time, energy and cost. In this research, a navigation system called ResLoc is being proposed. This system will help user especially for the food lovers in finding their favourite restaurants around Kota Bharu. This route-finding problem is one of the most important computer applications in the transportation industry. In network theory, it’s known as the shortest-path problem, and Dijkstra’s algorithm is usually used to solve it. Dijkstra’s algorithm is one of the classic shortest path search algorithms. Dijkstra’s algorithm is the technique that can solve the problem by itself. The algorithm searches in a weighted directed network to find the shortest path from a given node to every other node in the network. For the result, Djikstra’s algorithm will find the shortest path towards the desired restaurants regarding to the user current locations besides the system will also generate map towards the locations.